2003
DOI: 10.1046/j.1471-4159.2003.01965.x
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization‐induced ERK phosphorylation depends on the cytosolic Ca2+ level rather than on the Ca2+ channel subtype of chromaffin cells

Abstract: The contribution of Ca 2+ entry through different voltage-activated Ca 2+ channel (VACC) subtypes to the phosphorylation of extracellular signal regulated kinase (ERK) was examined in bovine adrenal-medullary chromaffin cells. High K + depolarization (40 mM, 3 min) induced ERK phosphorylation, an effect that was inhibited by specific mitogen-activated protein kinase kinase inhibitors. By using selective inhibitors, we observed that depolarization-induced ERK phosphorylation completely depended on protein kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…O'Farrell and Marley (293) observed that the individual blockade of a given calcium channel subtype was not enough to prevent the activation of tyrosine hydroxylase by K ϩ depolarization; however, blocking various calcium channel subtypes abolished the enzyme activation. This was also true for the Ca 2ϩ -dependent K ϩ -evoked increase in the expression of the exocytotic protein SNAP-25 (170) as well as for ERK phosphorylation, which seems to depend on a critical [Ca 2ϩ ] c rather than on activation of a given calcium channel subtype (260). We have also found that secretory control by mitochondrial Ca 2ϩ fluxes critically depends on the ability of K ϩ depolarization to create high [Ca 2ϩ ] c microdomains, rather than on Ca 2ϩ entry through a given calcium channel subtype (268).…”
Section: F Specialization Of Calcium Channel Subtypesmentioning
confidence: 75%
“…O'Farrell and Marley (293) observed that the individual blockade of a given calcium channel subtype was not enough to prevent the activation of tyrosine hydroxylase by K ϩ depolarization; however, blocking various calcium channel subtypes abolished the enzyme activation. This was also true for the Ca 2ϩ -dependent K ϩ -evoked increase in the expression of the exocytotic protein SNAP-25 (170) as well as for ERK phosphorylation, which seems to depend on a critical [Ca 2ϩ ] c rather than on activation of a given calcium channel subtype (260). We have also found that secretory control by mitochondrial Ca 2ϩ fluxes critically depends on the ability of K ϩ depolarization to create high [Ca 2ϩ ] c microdomains, rather than on Ca 2ϩ entry through a given calcium channel subtype (268).…”
Section: F Specialization Of Calcium Channel Subtypesmentioning
confidence: 75%
“…1998; Polo‐Parada et al. 2006), protein kinase activation (Mendoza et al. 2003), and gene expression (García‐Palomero et al.…”
mentioning
confidence: 99%
“…Therefore, ACCs were incubated with 10 μM of U0126, or its inactive analog U0124, 15 min prior to experimentation and throughout the test. In these conditions, U0126 efficiently inhibits ERK1/2 phosphorylation (Evans et al, 2002; Mendoza et al, 2003). …”
Section: Resultsmentioning
confidence: 99%
“…Both types of phosphorylation determine cortactin activity as well as its association with proteins such as the N-WASP (Martinez-Quiles et al, 2004; Tehrani et al, 2007; Kelley et al, 2011), an actin NPF that accumulates at exocytosis sites together with the Arp2/3 nucleation complex and F-actin (Gasman et al, 2004). In ACCs, both ERK1/2 and Src kinases are activated by secretagogues and regulate exocytosis (Allen et al, 1996; Cox and Parsons, 1997; Mendoza et al, 2003). As we recently reported, Src kinases also control Ca 2+ -dependent actin polymerization and fusion pore lifetime in ACCs (Olivares et al, 2014).…”
Section: Introductionmentioning
confidence: 99%